VISITOR PERCEPTION OF THE OBJECT AND TOURIST ATTRACTION OF NAMALATU BEACH IN LATUHALAT VILLAGE, NUSSANIWE DISTRICT, AMBON CITY, MALUKU PROVINCE. - Sinaga, Ida Ronauli; Latupapua, Yosevita Th; Seipalla, Billy B (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2024)
This study was conducted in May June 2024, sample determination was carried out using the Purposive sampling technique where researchers deliberately selected visitors as research subjects then research participants aged at least 17 years and over because they were considered adults to provide relevant responses to the questions asked. The data analysis method used is the qualitative descriptive method. Data collection was carried out using the interview method using questionnaires, observation, documentation and literature studies. To analyze the data, namely using descriptive analysis based on data obtained both through questionnaires and interviews and then described using percentage analysis. The results of this study indicate that visitor perceptions of attractions are 61% dominated by the highest value, related to accessibility 94%%, related to facilities 94% and ansileri 96%. The factors that influence visitor perceptions of the objects and attractions of Namalatu Beach tourism are related to internal factors, namely 92% and related to external factors, namely 100%.